2022
DOI: 10.1108/ijis-11-2021-0216
|View full text |Cite
|
Sign up to set email alerts
|

University industry collaboration process: a systematic review of literature

Abstract: Purpose The innovation process demands an interaction between environment agents, knowledge generators and policies of incentive for innovation and not only development by companies. Universities have gradually become the core of the knowledge production system and, therefore, their role regarding innovation has become more important and diversified. This study is aimed at identifying the mechanisms of university–industry (U–I) collaboration, as well as the operationalization steps of the U–I collaboration pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
0
3
0
2
Order By: Relevance
“…The most common types of collaboration between universities and industry are consultancy, contract research, joint research, training, conferences, meetings, and informal knowledge exchange. These common types of collaboration are some of the most effective partnerships; for instance, scholars (Baleeiro Passos et al 2022) showed that interactions between universities and industry professionals have improved the organization's performance and competitive advantage in the market. Human resource mobility is one of the most essential elements of such partnerships, having long-term benefits for the organization.…”
Section: Strategic Partnerships With Higher Education Institutionsmentioning
confidence: 99%
“…The most common types of collaboration between universities and industry are consultancy, contract research, joint research, training, conferences, meetings, and informal knowledge exchange. These common types of collaboration are some of the most effective partnerships; for instance, scholars (Baleeiro Passos et al 2022) showed that interactions between universities and industry professionals have improved the organization's performance and competitive advantage in the market. Human resource mobility is one of the most essential elements of such partnerships, having long-term benefits for the organization.…”
Section: Strategic Partnerships With Higher Education Institutionsmentioning
confidence: 99%
“…Publikowane wyniki badań na temat współpracy N-P są często sprzeczne i zależne od kontekstu w jakim są analizowane (6). W literaturze naukowej identyfi kuje się wiele mechanizmów współpracy N-P (7). Jednak nie aż tak wielu autorów badań postrzega przemysł jako partnera w relacji N-P oraz dostrzega wagę aspektów menedżerskich (7).…”
Section: Współpraca Nauka-przemysłunclassified
“…W literaturze naukowej identyfi kuje się wiele mechanizmów współpracy N-P (7). Jednak nie aż tak wielu autorów badań postrzega przemysł jako partnera w relacji N-P oraz dostrzega wagę aspektów menedżerskich (7).…”
Section: Współpraca Nauka-przemysłunclassified
See 2 more Smart Citations